IDENTIFICATION OF PORIFERA USING EDNA IN THE CORALS OF TAKAT, SUMENEP, EAST JAVA - Qotimah, Putri Nurul; Nugraha, Wajyu Andy; Nugraha, Insafitri (Jurnal Perikanan Unram, 2025)
Karang Takat is a body of water in Sumenep, Madura which has beauty and various kinds of flora and fauna, one of which is Porifera. Porifera are organisms that have an important role in coral reef ecosystems. Porifera live attached to coral reefs and stick to hard coral, because hard coral is a hard substrate for Porifera to stick to. Habitats with hard substrates will be places where porifera grow well, because only 10% of porifera can live. This research was conducted to provide an accurate and latest method for detecting the presence and diversity of Porifera. The eDNA metabarcoding method is suitable for identifying flora and fauna diversity, such as Porifera, with identification based on DNA residues left in their habitat. DNA species can be detected from species that release mitochondria, mucus, and excretory waste products into the environment. The results of Porifera DNA research in Karang Takat found 10 families, namely the Clionaide family, Niphatidae family, Tethyidae family, Spirastrellidae family, Desmacellida family, Chalinidae family, Microcionidae family, Astroscleridae family, Geodiidae family, and Halisarcidae family. The result was 11 species of Porifera from the same class. Known species are Spheciospongia semilunaris, Amphimedon sp, Tethya irisae, Spirastrella sp, Desmacella cf, Haliclona toxia, Clathria reinwardti, Stromatospongia vermicola, Haliclona amboinensis, Geodia sp., and Halisarca caerulea.